2011
DOI: 10.2337/dc11-1620
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Markers of Nucleic Acid Oxidation and Long-Term Mortality of Newly Diagnosed Type 2 Diabetic Patients

Abstract: OBJECTIVEWe analyzed data from a cohort of 1,381 newly diagnosed type 2 diabetic patients to test the hypothesis that urinary markers of nucleic acid oxidation are independent predictors of mortality.RESEARCH DESIGN AND METHODSWe examined the relationship between urinary excretion of markers of DNA oxidation (8-oxo-7,8-dihydro-2′-deoxyguanosine [8-oxodG]) and RNA oxidation (8-oxo-7,8-dihydroguanosine [8-oxoGuo]) and long-term mortality using Cox proportional hazards regression.RESULTSAfter multivariate adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 8 publications
5
55
0
1
Order By: Relevance
“…In this study, we demonstrate that 8‐oxo‐2′‐dG, a marker of oxidative damage, is independently associated with all‐cause mortality and cardiovascular mortality in adults with longstanding type 2 diabetes mellitus who participated in the ADVANCE trial. This finding is consistent with smaller observational studies linking survival of patients with diabetes mellitus to other markers of oxidative stress, including oxidized RNA,10, 11 derivatives of reactive oxygen metabolite,19 advanced autoxidation products,2, 20 and F‐isoprostanes 2, 20. However, this is the first large prospective study to confirm an independent association between mortality and 8‐oxo‐2′‐dG in type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we demonstrate that 8‐oxo‐2′‐dG, a marker of oxidative damage, is independently associated with all‐cause mortality and cardiovascular mortality in adults with longstanding type 2 diabetes mellitus who participated in the ADVANCE trial. This finding is consistent with smaller observational studies linking survival of patients with diabetes mellitus to other markers of oxidative stress, including oxidized RNA,10, 11 derivatives of reactive oxygen metabolite,19 advanced autoxidation products,2, 20 and F‐isoprostanes 2, 20. However, this is the first large prospective study to confirm an independent association between mortality and 8‐oxo‐2′‐dG in type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 89%
“…Urinary 8‐oxo‐2′‐dG has been independently associated with cardiovascular disease (CVD) in population cohorts4, 5, 6 and long‐term survival in patients with advanced CKD,7 heart failure (HF),8, 9 or cancer 2, 3. Yet, despite the recognized role of oxidative stress in diabetic complications, previous studies reported that spot urinary levels of 8‐oxo‐2′‐dG at diagnosis were not associated with subsequent mortality in Danish patients with type 2 diabetes mellitus 10, 11. This surprising finding may reflect the challenges of quantitative urinalysis in patients with type 2 diabetes mellitus in the community, especially when patients are poorly controlled (with polyuria and hyperfiltration) or have renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…IsoP and 8-OHdG are among the most commonly reported markers, in part due to their stability in vivo (Akagi et al, 2003; Milne et al, 2007). 8-oxoG is comparatively less common, but increasingly important (Poulsen et al, 2012); for example, urinary 8-oxoG (but not 8-OHdG) predicted long-term mortality from type 2 diabetes in a recent study (Broedbaek et al, 2011). Although all three markers are considered indicators of oxidative stress, they do not always correlate with one another (Watters et al, 2009), and they may differ for several reasons – e.g., DNA, RNA and lipids differ in their proximity to mitochondria, the primarily producer of ROS, they employ different mechanisms of repair or elimination, and each damage signature may have different pathophysiological consequences (Furukawa et al, 2004; Poulsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated markers of oxidative stress are associated with human obesity (Keaney et al, 2003), diabetes (Keaney et al, 2003), and cardiovascular mortality (Roest et al, 2008). Further, 8-hydroxyguanosine (8-oxoG), a marker of RNA oxidation, prospectively predicts long-term mortality among patients with diabetes (Broedbaek et al, 2011). Chronic psychological stress (e.g., caring for a spouse with dementia) has also been associated with heightened levels of both 8-oxoG and the oxidative byproduct F2-Isoprostanes (Epel et al, 2004b; Aschbacher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%